Developing air cargo operations at regional airports - Budd, Tom; Ison, Stephen; Budd, Lucy (Thomas Telford (ICE Publishing), 2015)
East Midlands airport (EMA) is a regional airport in northwest Leicestershire in central England. It is located roughly equidistant between the three Midlands' cities of Derby, Leicester and Nottingham and currently supports a range of full-service scheduled, charter and low-cost passenger operations to short- and medium-haul destinations in Europe as well as a significant number of long-haul intra and intercontinental freight services. In 2012, EMA was the thirteenth busiest passenger airport in the UK, handling just over four million customers a year, and the country's largest pure freight facility, processing almost 300 000 t of cargo and mail. By examining the historical development and commercial evolution of EMA from its opening as a commercial airport in 1965 to the present day, the paper details how a combination of far-sighted planning decisions and strategic management interventions have enabled EMA to diversify its operations and develop a unique operating niche that serves passenger flights during the day and cargo operations at night. The paper concludes by identifying elements of best practice and examining the extent to which the development of successful cargo operations at EMA could serve as a model for other regional airports worldwide that are seeking to develop complementary passenger and freight services.
Keywords: Airports; Logistics; Management